Design and analysis of linear switched reluctance motor - M. Asyraff Md. Aris; R. N. Firdaus; F. Azhar; N. A. Mohd Nasir; M. Z. Aishah (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This paper proposes a linear switched reluctance motor (LSRM) to replace the conventional serving that is used in food and beverage (F&B) applications such as a pack of sushi and carbonated drinks. This conventional method is no longer practical as it requires a lot of space which will affect costing and productivity. It’s also has another disadvantage, in which it needs frequent maintenance of the rotational motor, gear, and limit switches. Therefore, this research is about the design and analysis of linear switched reluctance motor (LSRM) for F&B applications. The main objective is to design a LSRM and the finite element method (FEM) is used to simulate the result. The result showed that the 24s/16p was the best model for linear switched reluctance motor (LSRM) design. The model had average force (F_avg) of 28.36 N for input current (I) of 1A. To conclude, this paperprovides a guideline in designing the LSRM for F&B application.